Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1538/expanim.21-0064
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of ADAM8 attenuates angiotensin II-induced cardiac fibrosis and endothelial-mesenchymal transition via inhibiting TGF-β1/Smad2/Smad3 pathways

Abstract: Endothelial-to-mesenchymal transition (EndMT) is involved in cardiac fibrosis induced by angiotensin II (Ang II). A disintegrin and metalloproteinase 8 (ADAM8), a member of ADAMs family, participates in cell adhesion, proteolysis and various signaling.However, its effects on the development of cardiac fibrosis remain completely unknown. This study aimed to reveal whether ADAM8 aggravates cardiac fibrosis induced byAng II in vivo and in vitro. The C57BL/6J mice or cardiac endothelial cells were subjected to Ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…TGF-β1-Smad2/Smad3 signaling pathway, as a member of TGF-β superfamily, plays different roles in cell proliferation, migration, differentiation, adhesion, death and other processes, as well as in embryonic development, formation of extracellular matrix, bone formation and reconstruction and other physiological processes [70,71]. Some studies have shown that in the classic TGF-β1 pathway, TGF-β1 can combine with TbR and TbR receptors on the cell surface to form trimer complexes, which can phosphorylate Smad2/3 itself in the cell and form complexes with Smad4 to promote nuclear translocation, and enter the nucleus to start the synthesis and secretion of factors related to proliferation and migration [72].…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β1-Smad2/Smad3 signaling pathway, as a member of TGF-β superfamily, plays different roles in cell proliferation, migration, differentiation, adhesion, death and other processes, as well as in embryonic development, formation of extracellular matrix, bone formation and reconstruction and other physiological processes [70,71]. Some studies have shown that in the classic TGF-β1 pathway, TGF-β1 can combine with TbR and TbR receptors on the cell surface to form trimer complexes, which can phosphorylate Smad2/3 itself in the cell and form complexes with Smad4 to promote nuclear translocation, and enter the nucleus to start the synthesis and secretion of factors related to proliferation and migration [72].…”
Section: Discussionmentioning
confidence: 99%
“…42 On the other hand, ADAM8 (a disintegrin and metalloproteinase 8), annotated from cg00805360, is reported to play a crucial role in the regulation of endothelial-to-mesenchymal transition and lead to cardiac fibrosis in response to Ang II (angiotensin II) infusion, indicating involvement in BP regulation. 43 The cg00574958 in CPT1A has previously been associated with triglyceride and blood glycemic levels, in addition to BP. 44,45 Previous studies have demonstrated that the methylation of cg00574958 regulates the expression of CPT1A and plays a vital role in maintaining blood glucose levels and glucose metabolism, which could affect the risk of downstream phenotypes, suggesting a possible modulating effect on BP.…”
Section: Discussionmentioning
confidence: 99%
“…There are other Brg1 targets that deserve to be closely examined for their roles in renal fibrosis in future studies. For instance, ADAM8 expression has been shown to respond to pro-fibrogenic stimuli in lung fibroblasts(59), cardiac fibroblasts(60), and dermal fibroblasts(61). Consistently, genetic deletion or pharmaceutical inhibition of ADAM8 attenuates fibrosis in the lungs(62) and in the skull(63).…”
Section: Discussionmentioning
confidence: 99%